CNC trade secrets : a guide to CNC machine shop practices - Harvey, James A. (Machinist) (Industrial Press, Inc., 2015)
This book is about computer numerical control (CNC) machine shop practices. Features include: over 100 4-color photos throughout; easy-to-read steps for going from print to part using CAD/CAM equipment; useful techniques for holding and machining parts using CNC machines; ways to unravel the mysteries of using G-code; ways to avoid crashing; 3D CNC milling basics; what CNC machines can and cannot do; solidworks challenges to improve your modeling skills; ideas for how engineers and designers can help machinists get the job done; practical and proven machining tips and tricks. --